TRAUMATIC EXPERIENCES IN FREDRIK BACKMAN’S A MAN CALLED OVE - Hormati, Prastika Wulandari; Mogea, Tini; Olii, Sanerita T. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to find out trauma to the main character in the novel A Man Called Ove and its causes. Ove experiences the loss of people he loves, which brings trauma to Ove’s life. The data are taken from monologue and dialogue with the other characters in the novel. This research uses a qualitative approach and Sigmund Freud’s psychological critisicm theory. The primary source is Fredrik Backman’s 2013 novel A Man Called Ove, while secondary sources include various related publications and online recources that provide credence to the subject. The research results show that there are three types of trauma reactions. The first is a mental reaction, when Ove has difficulty concentrating and feels lost. The next is an emotional reaction, when his new neighbor couldn’t park the car and made him angry. The last one is a behavioral reaction, when Sonja died, Ove never set foot in the caffe they usedto go every Sunday. The writer also found causes of this trauma : Accident and Death. From all the data found in the novel, it proves that Ove experienced trauma and ultimately died